Friedrich Torberg, Forum, and the Anxiety of the Cultural Critic in the (Austrian) State. - Burri, Michael (Journal of Austrian Studies)
This article presents the bifurcated reception of Friedrich Torberg as an exemplary manifestation of the analytic dissociation of nation from state in scholarship on early Second Republic Austria. This dissociation is manifested in the reception of a welcome cultural Torberg (nation) and an unwelcome political Torberg (state). I argue, however, that the postwar cultural criticism of Torberg was shaped by a deep skepticism toward the modern state, while in Forum he created an intellectual outpost that spotlighted attacks on increasing state power in a newly independent Austria. The designs of the CIA-funded Congress for Cultural Freedom upon Torberg as well as judgments regarding his complicity in those designs belong to established scholarship on Torberg. This paper explores a different issue: What did Torberg himself think he was doing?